Sharing Cities Shaping Cities - Arcidiacono, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The sharing economy and collaborative consumption are attracting a great deal of interest due to their business, legal and civic implications. The consequences of the spreading of practices of sharing in urban environments and under daily dynamics are underexplored. This Special Issue aims to address if and how sharing shapes cities, the way that spaces are designed and lived in if social interactions are escalated, and the ways that habits and routines take place in post-individualistic society. In particular, the following key questions are of primary interest: Urban fabric: How is 'sharing' shaping cities? Does it represent a paradigm shift with tangible and physical reverberations on urban form? How are shared mobility, work, inhabiting reconfiguring the urban and social fabric? Social practices: Are new lifestyles and practices related to sharing changing the use and design of spaces? To what extent is sharing triggering a production and consumption paradigm shift to be reflected in urban arrangements and infrastructures? Sustainability: Does sharing increase the intensity of use of space and assets, or, rather, does it increase them to meet the expectations of convenience for urban lifestyles? To what extent are these phenomena fostering more economically-, socially-, and environmentally-sustainable practices and cities? Policy: How can policy makers and municipalities interact with these bottom-up and phenomena and grassroots innovation to create more sustainable cities? Scholars responded to the above questions from the fields of urban studies, urban planning and design, sociology, geography, theoretically-grounded and informed by the results of fieldwork activities.